ESTIMATION OF RESEARCH & DEVELOPMENT EXPENDITURES AT UNIVERSITIES: SEARCHING RESPONSE - E. Sycheva; T. Tazikhina (Вестник университета)
The necessity, possibility and conditions of performed by Universities research and development works evaluation, as well as research & development work disclosure as a value appraisal object, economic value added multistage process and proposition of justified methods of its valuation have revealed. The value of research and development work performed by government-run educational institutions - Universities has examined. The necessity of the authors’ paper has conditioned, that Research and development works performed by Universities become the evaluation objects of the digital economy. The specific factors of research and development work evaluation are uniqueness, innovativeness, riskiness, affect not only their cost, but also require specificity in their evaluation. It is necessary to harmonize accountable appraisal tools for the evaluation of research and development work.